Papel da proteína Mx1 na resposta a interferons e no processo neoplásico - Brantis-de-Carvalho, C. E. [UNESP]; Boldrin, P. E. G. [UNESP]; Silva, W. A.; Rahal, Paula [UNESP]; Tajara, E. H.; Carraro, D. M.; Camargo, A. A.; Zanelli, C. F. [UNESP]; Valentini, S. R. [UNESP] (My University, 2011)
The Mx1 protein is encoded by an interferon- induced gene and shares domain organization, homooligomerization capacity and membrane association with the large dynamin-like GTPases. The Mx1 protein is involved in the response to a large number of RNA viruses, such as the bunyavirus family and the influenza virus. Interestingly, it has also been found as a methylation-silenced gene in several types of neoplasm, including head and neck squamous cell carcinoma. In this scenario, MX1 gene silencing is associated with immortalization in several neoplastic cell lines. Thus, Mx1 stands out as one of the key proteins involved in interferon-induced immune response and also plays an important role in cell cycle control. Here we discuss some of the functions of the Mx1 protein, including its antiviral activity, protein folding and involvement in neoplasia, as well as those revealed by investigating its cellular partners.

A proteína Mx1 é codificada por um gene induzido por interferon e compartilha a organização de seus domínios, a capacidade de homo-oligomerização e associação com membranas com as grandes dinaminas GTPases. A proteína Mx1 está envolvida na resposta contra um grande número de vírus de RNA, como aqueles pertencentes à família Buniavírus e o vírus influenza. Curiosamente, o gene MX1 foi encontrado como silenciado por metilação em diversos processos neoplásicos, incluindo carcinomas de cabeça e pescoço de células escamosas. Neste cenário, o silenciamento gênico de MX1 está associado à imortalização de uma série de linhagens celulares neoplásicas. Assim, Mx1 se destaca como uma das principais proteínas envolvidas nas respostas imunes induzidas por interferon e também desempenha um importante papel no controle do ciclo celular. Aqui discutimos os aspectos funcionais da proteína Mx1 abordando sua atividade antiviral, organização estrutural, envolvimento com neoplasias e, principalmente, os aspectos funcionais obtidos pela determinação de seus parceiros celulares. Palavras-Chave: Interferons. MX1. JAK/STAT. Vírus. Neoplasia. PML-NBs. SUMOilação.
Role of Mx1 protein in the response to interferons and neoplastic process
Keywords: Interferons; JAK/STAT; MX1; Neoplasia; PML-NBs; SUMOylation; Virus; interferon; mx1 protein; protein derivative; unclassified drug; antiviral activity; Bunyavirus; cancer cell culture; cell immortalization; gene silencing; head and neck squamous cell carcinoma; immune response; Influenza virus; methylation; oncogenesis and malignant transformation; protein folding; protein function; RNA virus